An assessment of place brand potential: familiarity, favourability and uniqueness. Issue 3 (10th October 2016) - Chan, Chung-Shing; Peters, Mike; Marafa, Lawal M.
Abstract : Purpose: This paper aims to present an approach by which to assess the potential of branding a particular type of place resource or feature. Design/methodology/approach: A review was conducted to analyse three key periodicals ( Journal of Brand Management, Place Branding and Public Diplomacy and Journal of Place Management and Development ) in the field of branding and place branding between 2000 and 2011. These three periodicals are recognized as the three leading periodicals of place branding, and they followed the clear establishment and development of the field of place branding. Findings: Familiarity, favourability and uniqueness are the three dimensions that give a quick indication of the level of place brand equity, and in turn they represent the level of place brand potential. Research limitations/implications: In the literature, brand potential is not well conceptualized. This paper identifies this knowledge gap through a review of place branding studies, and it closes the gap by connecting brand potential with place brand equity. Originality/value: This paper suggests practical and research directions by which to study these three dimensions to generate valuable brands for places.